2017
DOI: 10.1016/j.vaccine.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster vaccine live: A 10 year review of post-marketing safety experience

Abstract: Background Zoster vaccine is a single dose live, attenuated vaccine (ZVL) indicated for individuals ≥50 years-old for the prevention of herpes zoster (HZ). Safety data from clinical trials and post-licensure studies provided reassurance that ZVL is generally safe and well tolerated. The objective of this review was to provide worldwide post-marketing safety information following 10 years of use and >34 million doses distributed. Methods All post-marketing adverse experience (AE) reports received worldwide be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 33 publications
3
62
0
5
Order By: Relevance
“…6,7 Vaccination has the potential to provide long-term protection against herpes zoster, but live attenuated vaccines are contraindicated in immunocompromised individuals because of the risk of varicella resulting from spread of the vaccine strain. 8,9 An adjuvanted recombinant zoster vaccine, consisting of the varicella-zoster virus glycoprotein E antigen and the AS01 B adjuvant system, is nonlive and has no associated risk of triggering the infection in healthy adults. 10 This vaccine significantly reduced herpes zoster risk in adults aged at least 50 and at least 70 years (vaccine efficacy, 91%) and has been licensed in several countries.…”
mentioning
confidence: 99%
“…6,7 Vaccination has the potential to provide long-term protection against herpes zoster, but live attenuated vaccines are contraindicated in immunocompromised individuals because of the risk of varicella resulting from spread of the vaccine strain. 8,9 An adjuvanted recombinant zoster vaccine, consisting of the varicella-zoster virus glycoprotein E antigen and the AS01 B adjuvant system, is nonlive and has no associated risk of triggering the infection in healthy adults. 10 This vaccine significantly reduced herpes zoster risk in adults aged at least 50 and at least 70 years (vaccine efficacy, 91%) and has been licensed in several countries.…”
mentioning
confidence: 99%
“…The single dose, lyophilized, live, attenuated VZV vaccine (i.e., zoster vaccine live (Zvl), Zostavax, Merck) is indicated for prevention of latent VZV reactivation leading to shingles in individuals older than 50 years. ZVL is licensed in over 55 countries, with 34 million distributed doses globally (Willis et al, 2017), and which has associated efficacy rates of over 50% in all ages tested (Oxman et al, 2005;Schmader et al, 2012); consistent with original clinical trial datasets (Tseng et al, 2011;Langan et al, 2013;Marin et al, 2015). However, increases in VZV susceptibility have arisen due to increasing aging populations, and in immune-suppressed organ transplant recipients, chemotherapy patients, HIV-infected individuals, and those suffering from chronic illnesses (Forbes et al, 2014).…”
Section: Vzv Classification Epidemiology Immunology and Vaccinologymentioning
confidence: 92%
“…8 Analysis of all worldwide post-marketing adverse events (2006-2016) following ZVL found that disseminated HZ was reported in <1% of cases. 9 This suggests that while such an event can occur, it is uncommon. Given the significant morbidity seen with HZ, 10 we would suggest the benefit of ZVL, even in the setting of LFN is worth the riskafter discussion with the patient regarding the benefit/risk ratio.…”
Section: Author Replymentioning
confidence: 99%
“…8 While most of the 4826 patients who were immunosuppressed around the time of ZVL had only low-dose prednisone, 126 of them were taking LFN. 9 This suggests that while such an event can occur, it is uncommon. 9 This suggests that while such an event can occur, it is uncommon.…”
mentioning
confidence: 99%